2017
DOI: 10.1080/03007995.2017.1331211
|View full text |Cite
|
Sign up to set email alerts
|

The burden of hepatorenal syndrome among commercially insured and Medicare patients in the United States

Abstract: HRS imposes a significant economic burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 10 publications
1
19
1
Order By: Relevance
“…The costs of AC and non‐AC also approximate the range of per‐person yearly costs of cancer patients regardless of treatment (21,000‐90,000 US$ in commercially insured persons) . Our estimates of yearly costs of managing decompensated cirrhosis, hepatorenal syndrome, and HCC are similar to published cost estimates, supporting the robustness of our cost estimates . In studies of the global burden of AC, its disability‐adjusted life‐year burden exceeded that of other alcohol‐related malignancies .…”
Section: Discussionsupporting
confidence: 82%
“…The costs of AC and non‐AC also approximate the range of per‐person yearly costs of cancer patients regardless of treatment (21,000‐90,000 US$ in commercially insured persons) . Our estimates of yearly costs of managing decompensated cirrhosis, hepatorenal syndrome, and HCC are similar to published cost estimates, supporting the robustness of our cost estimates . In studies of the global burden of AC, its disability‐adjusted life‐year burden exceeded that of other alcohol‐related malignancies .…”
Section: Discussionsupporting
confidence: 82%
“…Finally, the two studies differ in patient characteristics that may impact costs, including transplant rates. Whereas Rice et al 21 reported transplant rates of 10.7% for their commercial population and 1.6% for the Medicare population, our study population, from all payer sources, had a 2.1% transplant rate overall. The high cost of transplants and vastly different rates of transplants may be key differences in the observed costs.…”
Section: Discussioncontrasting
confidence: 57%
“…Previous studies have reported markers and assessments to estimate HRS resource utilization. However, drivers of total charges remain relatively unclear 21 . We created a generalized linear model to extend our initial findings to include characteristics that are statistically significant with respect to total visit charges for all patients, including length of stay, teaching hospital status, patients on dialysis, mortality, transfer to skilled nursing facility, or inpatient setting ( Supplementary Tables S3-S6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Another study described the prevalence of HRS in about 48% of patients listed for LT. 5 Apart from negative impact on patient survival and outcomes, HRS is associated with huge healthcare cost and significant socio-economic burden. 6 For example, in a retrospective study on 2542 patients hospitalized with HRS, mean length of hospital stay per patient was 30.5 days, with $91,504 per admission. 7…”
Section: Introductionmentioning
confidence: 99%